Evaluation of the influence of surface finishing on the corrosion resistance of HVOF applied inconel 625 coatings on steel - Lorenzi, Mariana Sgambaro de (2019)
In this work, the corrosion resistance of Inconel 625 coatings applied to AISI 4140 steel plates was evaluated. Coatings were produced by High Velocity Oxygen Fuel (HVOF) by use of two different equipment which use either kerosene (liquid) or propane (gas) as fuel. The resulting coatings were evaluated in two conditions: as-deposited and after a surface finishing process by grinding. Residual stress distributions in the coatings were characterized by X-ray diffraction and their morphology was verified through metallography and roughness measurements. Potentiodynamic polarization corrosion testing complemented their analysis. The results show a strong influence of the surface finishing process on the corrosion performance of the coatings.